The impact of COVID‐19 on cancer care of outpatients with low socioeconomic status. Issue 1 (17th February 2022) - Zeilinger, Elisabeth L.; Lubowitzki, Simone; Unseld, Matthias; Schneckenreiter, Carmen; Heindl, Daniel; Staber, Philipp B.; Raderer, Markus; Valent, Peter; Zöchbauer‐Müller, Sabine; Bartsch, Rupert; Prager, Gerald; Jaeger, Ulrich; et al.
Abstract: Patients with low socioeconomic status (SES) are among the most underserved groups of people regarding cancer care. Analyzing the impact of the coronavirus‐induced disease 2019 (COVID‐19) pandemic on health care disparities and calling attention to inequalities in cancer care is crucial to justify and initiate adequate countermeasures. We aimed to determine whether the COVID‐19 pandemic aggravated health care disparities of cancer outpatients related to their SES and analyzed patient data of the largest university center providing services for patients with hematologic and oncologic disorders in Austria from 2018 to 2021. SES was assessed using three indicators: monthly net household income, level of education and occupational prestige. In total, 1217 cancer outpatients (51.1% female) with a mean age of 59.4 years (SD = 14.2) participated. In the first year of the pandemic, the relative proportion of individuals with low income, low education level and low occupational prestige seeking cancer care at our outpatient center decreased significantly ( P  ≤ .015). The strongest indicator was income, with a consistent effect throughout the first pandemic year. Countermeasures and specific interventions to support cancer patients with low SES in their access to health care should be initiated and prioritized. Abstract : What's new? The COVID‐19 pandemic caused disruptions to cancer care all over the world. But has it also worsened existing healthcare disparities for patients with low socioeconomic status? Here, using data from a European welfare state where patients have easy access to cancer treatment regardless of their employment or insurance status, the authors compared the socioeconomic status of cancer outpatients who received treatment before and during the pandemic. In the first year of the pandemic, people with low socioeconomic status were seeking cancer care significantly less frequently than before the pandemic. Countermeasures to reach this underserved patient group are needed.